2016
DOI: 10.1186/s12906-016-1432-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Nigella sativa on thyroid function, serum Vascular Endothelial Growth Factor (VEGF) – 1, Nesfatin-1 and anthropometric features in patients with Hashimoto’s thyroiditis: a randomized controlled trial

Abstract: BackgroundHashimoto’s thyroiditis is an autoimmune disorder and the most common cause of hypothyroidism. The use of Nigella sativa, a potent herbal medicine, continues to increase worldwide as an alternative treatment of several chronic diseases including hyperlipidemia, hypertension and type 2 diabetes mellitus (T2DM). The aim of the current study was to evaluate the effects of Nigella sativa on thyroid function, serum Vascular Endothelial Growth Factor (VEGF) – 1, Nesfatin-1 and anthropometric features in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…Written informed consent was obtained from all of the participants before participation in the trial and the study protocol was approved by the ethics committee of Tabriz University of Medical Sciences (Project number: 93173). The current trial was also registered in the Iranian Registry of Clinical Trials (Identifier: IRCT2014090819082N2) [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all of the participants before participation in the trial and the study protocol was approved by the ethics committee of Tabriz University of Medical Sciences (Project number: 93173). The current trial was also registered in the Iranian Registry of Clinical Trials (Identifier: IRCT2014090819082N2) [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Daily consumption of 2 g N. sativa L. powder during 8 weeks has proved to be effective against hypothyroidism in forty patients, aged between 22 and 50 years old, suffering from Hashimoto’s thyroiditis. The beneficial effects of N. sativa L. have been attributed mainly to its antioxidant potential ( Farhangi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (1998) have reported that vascular endothelial growth factor (VEGF) and its receptors (Flt-1) contribute to the developmental regulation of thyroid epithelial cells in adult Wistar rats after administration of goitrogen for two weeks. Studies have revealed that thymoquinone decreases VEGF levels ( Sethi et al, 2008 ) which are known to increase in response to the increase of TSH concentrations in patients suffering from chronic thyroiditis or thyroid cancer ( Farhangi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, in all kinds of nuts, the zinc concentration ranges from 2.1 to 4.7 mg/100 g [27,28,29]. Farhangi et al [76] showed the potential beneficial effect of powdered seeds of Nigella sativa in improving thyroid status and anthropometric variables in patients with HT. Nevertheless, its function on the human thyroid requires more trials, and this finding should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%